C-kit is important for SOD1G93A mouse survival independent of mast cells. (20th August 2015) - Staats, K.A.; Schönefeldt, S.; Van Helleputte, L.; Van Rillaer, M.; Lampi, Y.; Dooley, J.; Van Den Bosch, L.; Liston, A.
Highlights: Kit knockdown decreases survival of SOD1 G93A mice, but does not alter motor neuron loss at end stage. Kit knockdown affects motor parameters in mice, without affecting the number of (motor) neurons. Pharmacological stabilization of mast cells does not affect SOD1 G93A mouse survival. Abstract: Amyotrophic Lateral Sclerosis (ALS) is a devastating neurodegenerative disease leading to progressive and lethal paralysis. The disease process is multi-factorial and is characterized by selective motor neuron degeneration. Previous work demonstrated that the local concentration of various growth factors can influence motor neuron survival and disease progression. A potential role for c-kit, a growth factor receptor present in the spinal cord, in ALS is unknown. To dissect the role of c-kit in ALS we interbred SOD1 G93A mice with kit w-sh/w-sh mice, which have a 70% decrease in c-kit expression in the spinal cord. kit w-sh/w-sh SOD1 G93A mice have a reduced survival compared to SOD1 G93A mice, while the amount of motor neurons at end stage is similar. By means of grip strength and nerve conductance analysis we show that kit w-sh/w-sh mice have diminished strength and slightly impaired compound muscle action potential latency, although the number of neurons is similar across genotypes. Decreasing kit gene expression in SOD1 G93A mice is detrimental and our results imply that this effect is independent of mast cells, as tested by ketotifen administration. To conclude, our data expand on the protective role of growth factors in ALS, as decreasing c-kit by approximately 70% is detrimental in SOD1 G93A mice.